Case Report: Next generation sequencing identifies a NAB2-STAT6 fusion in Glioblastoma - Diamandis, Phedias (Diagn Pathol, 2016)
BACKGROUND: Molecular profiling has uncovered genetic subtypes of glioblastoma (GBM), including tumors with IDH1 mutations that confer increase survival and improved response to standard-of-care therapies.  By mapping the genetic landscape of brain tumors in routine clinical practice, we enable rapid identification of targetable genetic alterations. CASE PRESENTATION: A 29-year-old male presented with new onset seizures prompting neuroimaging studies, which revealed an enhancing 5 cm intra-axial lesion involving the right parietal lobe. He underwent a subtotal resection and pathologic examination revealed glioblastoma with mitoses, microvascular proliferation and necrosis. Immunohistochemical (IHC) analysis showed diffuse expression of GFAP, OLIG2 and SOX2 consistent with a tumor of glial lineage. Tumor cells were positive for IDH1(R132H) and negative for ATRX. Clinical targeted-exome sequencing (DFBWCC Oncopanel) identified multiple functional variants including IDH1 (p.R132H), TP53 (p.Y126_splice), ATRX (p.R1302fs*), HNF1A (p.R263H) and NF1 (p.H2592del) variants and a NAB2-STAT6 gene fusion event involving NAB2 exon 3 and STAT6 exon 18. Array comparative genomic hybridization (aCGH) further revealed a focal amplification of NAB2 and STAT6.  IHC analysis demonstrated strong heterogenous STAT6 nuclear localization (in 20 % of tumor cells). CONCLUSIONS: While NAB2:STAT6 fusions are common in solitary fibrous tumors (SFT), we report this event for the first time in a newly diagnosed, secondary-type GBM or any other non-SFT. Our study further highlights the value of comprehensive genomic analyses in identifying patient-specific targetable mutations and rearrangements.